Diachronic Changes Underlying Synchronic Distribution Scalar Inferences and Word Order - Chen, I-Hsuan (Studies in East Asian Linguistics, 2018)
This book deals with synchronic variation in Chinese through a diachronic lens, based on the evidence from a quantitative, longitudinal corpus study. Departing from the traditional analysis in diachronic changes in Chinese linguistics, the cognitive constructionist approach employed in this book is able to capture incremental changes by combining syntax, semantics, and pragmatics. Topics such as word order, focus, scopes of quantifiers, information structure, and negation have been important issues in linguistics, but they are rarely integrated as a whole. The book makes their diachronic interactions available to the students and researchers in the fields of general and Chinese linguistics.